An uncommon woman - Frantz, Laura (Revell, 2019)
In the borderlands of 1770 West Virginia there is no place for finer feelings. Charged with keeping the peace with local tribes, a hero of the French and Indian War is determined to stay free of romantic entanglement--until he meets a frontier maiden who just might be able to change his mind.